Informal learning in work place: a case of caregivers - P, Keerthanaa; Suresh, M (International Journal of Engineering and Technology, 2018)
Dynamism and adaptive divergence in working environment in responsive to the ever changing knowledge world is an unavoidable factor contributing the growth of any industry. The informal learning gained naturally from day to day practices in healthcare organizations devel-ops an insight which would help to expand the quality of treatment. This motivates the people to learn to improve the treatment with the help of technology. The main objective of this research is to analyse the factors which impact the informal learning in the healthcare organization for the young adult age group (age between 18- 29) of the caregivers. By using the Interpretive Structural Modelling(ISM) finding the inter-relationship between the factors. Finally, the paper concludes with most influential factors feedback, individual level learning culture and team work learning culture which affecting the caregivers in hospitals. Â Â